ANTIOXIDANT DAN XANTHINE OXIDASE INHIBITORY STUDIES OF PARANG ROMANG (BOEHMERIA VIRGATA (FROST.) GUILL) DAN ISOLATION OF ACTIVE COMPOUND - Ikhlas Arsul, M
One of the plants used by the community as a medicinal material is the parang romang plant (Boehmeria virgata (Forst.) Guill). The leaves of this plant are traditionally used as a cure for cancer, pain, and itching by the people of South Sulawesi. The pharmacological activity of parang romang is still limited and not widely known. The purpose of this study was to characterize the crude drug of parang romang plant parts, examine the total phenol and flavonoid content, antioxidant activity and xanthine oxidase inhibition of parang romang plant parts, examine the antioxidant and xanthine oxidase inhibitory activities of extract fractions of selected parts of parang romang, examine the antioxidant and xanthine oxidase inhibitory activities of parang romang subfractions, characterize and identify the structure of active compounds of parang romang. This research includes four stages of work, namely characterization of parang romang crude drug, extraction and fractionation of active compounds by antioxidant and xanthine oxidase inhibitory activities guidance, isolation and purification of active compounds, and characterization of isolates. The plant parts to be used are roots, stems, leaves, and flowers, each extracted by reflux method using 96% ethanol solvent. Then, antioxidant activity and xanthine oxidase inhibitory activities were carried out on the extracts of the four plant parts. The selected extract was then subjected to extraction by reflux method using increasing polarity solvent, n-hexane, ethyl acetate, and ethanol. The selected extract was then fractionated by vacuum liquid chromatography (VLC) method; the selected fractions were then subfractionated by classical column chromatography (CCC) method; followed by purification and purity test; the isolates were tested their antioxidant and xanthine oxidase inhibitory activity; then the active compounds were characterized and n identified using thin layer chromatography, UV-visible spectrophotometry and nucelar magnetic reconance (NMR) spectrometry. The extraction results of roots, stem, leaves, and flowers from parang romang plants obtained yields of 6.5; 8.1; 19.2; and 6.5% and density of 1% (w/v in ethanol) extract of roots, stem, and flower 0.82 g/mL and leaves 0.81 g/mL. The results of phytochemical screening showed that the roots contained flavonoids, saponins, quinones, tannins, alkaloids, and coumarins; the stems and leaves contained flavonoids, alkaloids, coumarins, and steroids/triterpenoids; and the flowers contained flavonoids, saponins, quinones, alkaloids, coumarins, and steroids/triterpenoids. The highest total phenol content was found in the roots extract (509.93 ± 0.85 mg GAE/g extract), while the highest total flavonoid content was found in the flower extract (118.61 ± 1.82 QE/g extract). The highest antioxidant capacity by DPPH and CUPRAC methods was shown by roots extract 387.92 ± 0.24 mg AEAC/g extract and 105.78 ± 0.17 mg AEAC/g extract, while by FRAP method was shown by leaves extract 24.15 ± 1.09 mg AEAC/g extract. The highest IC50 of xanthine oxidase inhibition in leaves extracts was 11.53 ± 0.02 µg/mL. Next, parang romang leaves were done extraction by gradient solvent and obtained yields of 1.5; 2.7; and 7.2% with 1% extract density were 0.79, 1.05, and 0.98 for n-hexane, ethyl acetate, and ethanol extracts, respectively. The highest total phenol content of the selected part (leaves) was found in ethanol extract (248.21 ± 0.86 mg GAE/g extract), while the highest total flavonoid content was found in n-hexane extract (446.45 ± 13.09 QE/g extract). The highest antioxidant capacity was shown in the ethanol extract, which was 261.34 ± 0.50; 202.27 ± 2.25; and 123.32 ± 3.07 mg AEAC/g extract for DPPH, FRAP, and CUPRAC methods, respectively. The highest IC50 of xanthine oxidase showed in ethyl acetate extracts was 11.53 ± 0.02 µg/mL. Isolate M and I have succeeded isolated from ethyl acetate leaves extract and isolate A from n-hexane leaves extract. The isolates showed xanthine oxidase inhibitory activities with IC50 63.97 ± 0.40; > 200; and 8.94 ± 0.10 µg/mL, respectively and also have antioxidant activities. Isolat M, I, and A were quercitrin, scopoletin, and ursolic acid, respectively.